2020
DOI: 10.1038/s41467-019-13818-7
|View full text |Cite
|
Sign up to set email alerts
|

The ETFL formulation allows multi-omics integration in thermodynamics-compliant metabolism and expression models

Abstract: Systems biology has long been interested in models capturing both metabolism and expression in a cell. We propose here an implementation of the metabolism and expression model formalism (ME-models), which we call ETFL, for Expression and Thermodynamics Flux models. ETFL is a hierarchical model formulation, from metabolism to RNA synthesis, that allows simulating thermodynamics-compliant intracellular fluxes as well as enzyme and mRNA concentration levels. ETFL formulates a mixed-integer linear problem (MILP) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
90
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 56 publications
6
90
0
Order By: Relevance
“…We propose a dynamic method that tackles the challenges mentioned above and models diauxie at the proteome level. To this effect, we used our recently published framework for ME models, ETFL ( 19 ). The formulation of ETFL permits the inclusion of thermodynamics constraints in expression models, as well as the ability to describe the growth-dependent allocation of resources.…”
mentioning
confidence: 99%
“…We propose a dynamic method that tackles the challenges mentioned above and models diauxie at the proteome level. To this effect, we used our recently published framework for ME models, ETFL ( 19 ). The formulation of ETFL permits the inclusion of thermodynamics constraints in expression models, as well as the ability to describe the growth-dependent allocation of resources.…”
mentioning
confidence: 99%
“…Overall, the reduced size of the new models and their conceptual organization overcomes some of the main challenges in building genome-scale context-specific models as for example, the barrier of data network coverage. The reduced models generated with redHUMAN are powerful representations of the specific parts of the network, and they have promising applications as they are suitable to use with existing methods including MBA 62 , tINIT 34 , mCADRE 33 , uFBA 63 , GECKO 64 , ETFL 65 , TEX-FBA 66 , and IOMA 67 .…”
Section: Discussionmentioning
confidence: 99%
“…Salvy and Hatzimanikatis [123] published a variation on metabolism and expression models, also referred to as ME models [124], named Expression and Thermodynamics Flux models (ETFL), which are capable of incorporating metabolomics data as thermodynamic constraints that ensure proper directionality of reactions. In this approach, thermodynamically feasible fluxes are combined with proteomics and transcriptomics data.…”
Section: Integration Of Metabolomics With Multiple Omics Datamentioning
confidence: 99%
“…Integration of metabolomics and phosphoproteomics into a kinetic model to characterize the response to the insulin on the signaling and metabolic level [118] Kinetic model and constraint-based model Flux estimation from single-point unlabeled data by integrating it into a model which consists of a kinetic and constraint-based model [119] FBA with regulatory Boolean logic and kinetic model Genome-scale FBA modification that captures metabolism, regulation and signaling in E. coli [121] FBA and other constraint-based methods GIM3E, an approach to develop condition-specific models [122] ME model Thermodynamically consistent ME model [123] TREM-Flux dFBA variation used to integrate time-series metabolomics and transcriptomics data to study the response of Chlamydomonas to rapamycin treatment [109] Multicellular, multitissue and community modelling DFBA dFBA for co-cultures to study the metabolic interactions in microbial community [133] 13 C-MFA A peptide-based 13 C-MFA approach for co-cultures [134] 13 C-MFA 13 C-MFA for co-cultures [135] FBA FBA approach to study plant on the organismal level, highlighting differences in tissue-specific metabolic networks [136] FBA Cell-specific metabolic models are combined within single model allowing the study of complex physiological processes such as a Cori or alanine cycle [137] FBA A modelling study accounting for the interactions between cell types found in the brain is validated with experimental data and demonstrates metabolic interplays and activities that less detailed models are missing [138] FBA + FPM (functional plant model, special kind of kinetic model)…”
Section: Comment Referencementioning
confidence: 99%